Is there any Difference between Males and Females in Mindful Eating? - Weni Anissa Putri; Ari Widodo; Rini Solihat (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Mindful eating is a way of paying attention to food momentarily, without judgment, with a calm feeling that focuses on individual sensory and food experiences. Thus, this research investigates students' awareness of eating between females and males from secondary school. The participants are 95 students of VIII and IX grades in one public school. This research was conducted in the even semester of the 2023/2024 academic year. The method is descriptive data. The research subject completed to fulfill the Mindful Eating Questionnaire (MEQ). The dimensions of the mindful eating questionnaire are disinhibition, awareness, external cues, internal emotional response, and distraction. The average mindful eating dimension is disinhibition in males (58.24) and females (52.95), awareness in males (78.57%) and females (72.14%), External cues in males (75.42%) and females (72.14%), emotional response in males (76%) and g, (76.14%), and distraction in males (64.71%) and females (69.11%). Gender differences were found in mindful eating dimensions, with males having higher scores than females. However, emotional response and distraction dimensions are higher in females.